1964
DOI: 10.1177/001872086400600412
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Prediction of Problem Drivers

Abstract: The major aim was to develop personality-inventory scales for the discrimination between two groups of problem drivers—traffic violators and accident-repeater drivers—and better-than-average drivers. A secondary aim was to attempt to improve prediction of problem drivers through multiple-regression equations. An experimental instrument including 395 items was developed, taking into account a very wide variety of personal qualities that had previously been found to characterize problem drivers or that were new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Shaffer, Towns, Schmidt, Fisher, and Zlotowitz (1974) investigated a sample of fatally injured male drivers and found that these individuals were on average seen as more belligerent, negative, verbally expansive, hyperactive, and displaying more psychopathology than comparable normative males. Several studies demonstrated that many psychological and social factors such as aggressiveness, depression, and social maladjustment were significantly related to traffic accidents (Cresswell & Groggatt, 1963; McFarland & Moore, 1957a,b,c; McGuire, 1956; Schuster & Guildford, 1964).…”
Section: Methodsmentioning
confidence: 99%
“…Shaffer, Towns, Schmidt, Fisher, and Zlotowitz (1974) investigated a sample of fatally injured male drivers and found that these individuals were on average seen as more belligerent, negative, verbally expansive, hyperactive, and displaying more psychopathology than comparable normative males. Several studies demonstrated that many psychological and social factors such as aggressiveness, depression, and social maladjustment were significantly related to traffic accidents (Cresswell & Groggatt, 1963; McFarland & Moore, 1957a,b,c; McGuire, 1956; Schuster & Guildford, 1964).…”
Section: Methodsmentioning
confidence: 99%
“…Quimby and Watts (1981) found that scores on a questionnaire measuring attitudes to driving behaviors and road safety were associated with age and with crash involvement. However, other studies failed to find associations between driving attitudes and crash involvement (Hakkinen, 1958(Hakkinen, ,1979Preston & Harris, 1965) or found them to be less strongly predictive than biographical variables (Schuster & Guilford, 1962).…”
Section: Driving Stylementioning
confidence: 97%
“…Arthur et al observed that unlike the variables in the other predictor categories (e.g., information processing), the personality variables seemed to be characterized by a lack of standardization. Several personality researchers have used unstandardized, ad hoc questionnaires, inventories, and tests developed specifically for the study in question (e.g., Clark, 1976;Schuster & Guilford, 1964).…”
Section: 32%mentioning
confidence: 99%